You want me to check your grammar again? The usefulness of an online grammar checker as perceived by students - Cavaleri, Michelle Rose; Dianati, Saib (Journal of Academic Language and Learning, 2016)
Feedback on students’ writing is considered an instrumental part of the academic advising process. However, due to the time constraints of the student-adviser interaction, Academic Language and Learning (ALL) advisers may find it difficult to provide comprehensive feedback to students regarding their grammatical mistakes. One solution is to utilise online grammar checking tools as a complement to feedback from an adviser. These tools can save advisers’ time and resources while at the same time promote greater self-directed learning and foster students’ self-efficacy. In spite of this, many Australian higher education institutions have overlooked this intersection between grammar support and online automated technology. This paper presents an overview of Grammarly, a popular online grammar checking website. In addition, this paper provides preliminary results of an evaluation of Grammarly by students at two Navitas colleges, the Australian College of Applied Psychology (ACAP) and Navitas College of Public Safety (NCPS). The students’ survey responses are analysed against Davis’ (1989) Technology Acceptance Model (TAM), which offers a conceptual framework for predicting the acceptability and use of a technology. The results reveal that students perceive Grammarly as useful and easy to use, and students reported that Grammarly improved their writing and understanding of grammar rules.